Analisis Strategi Pemasaran Marketing Mix untuk Meningkatkan Penjualan Pada D’Besto Fried Chicken Pekanbaru - Rinaldi, Afdhol (JAWI : Journal of Ahkam Wa Iqtishad, 2023)
Marketing strategy is an effort to market a product, both in the form of goods and services, using certain plans and tactics to increase sales volume. One of the business development strategies is the implementation of a marketing mix strategy. Marketing is one of the most important factors in the continuity of a business, so it is very important for business people to pay attention to the marketing mix in their business. The purpose of this study was to determine how D'besto Fried Chicken Pekanbaru applies sales promotion. The data analysis technique used is market mix analysis. The marketing mix variables studied were product, price, place and promotion. The results of this study indicate that consumer decisions in purchasing D'besto Fried Chicken Pekanbaru are strategic location selection and products that are acceptable to the public. The recommendation of this research is that D'besto Fried Chicken Pekanbaru products should be more diverse and innovative in terms of packaging and online marketing and improve brand quality.